Tantangan Implementasi Kebijakan Hukum Internasional terhadap Pencucian Uang Digital di Indonesia - Syarifah Faizah; Lisa Marina; Ani Purwati (Jurnal Riset Multidisiplin Edukasi, 2025)
The advancement of digital technology has significantly transformed the global financial system while also creating opportunities for transnational crimes, particularly technology-based money laundering. This study aims to examine the legal framework governing money laundering from both international and national perspectives, and to identify the challenges Indonesia faces in implementing related legal policies. The research employs a normative juridical method with a qualitative approach, based on literature review of international instruments such as the UNTOC and FATF standards, along with domestic regulations including Law No. 8 of 2010 on Money Laundering. The findings indicate that despite Indonesia's ratification of various international legal instruments, enforcement remains limited due to technological gaps, lack of skilled human resources, weak international cooperation, and low legal awareness among business actors. Therefore, there is an urgent need to strengthen legal diplomacy, optimize the use of advanced technology, enhance public legal education, and reform regulations to address the increasingly complex and cross-border nature of digital money laundering crimes.